Musik Dewa-Dewa Dalam Upacara Erau Pelas Benua di Guntung Kota Bontang Kalimantan Timur - Yusuf Rizky (SELONDING, 2018)
Erau Pelas Benua Guntung is the ritual ceremony that held by Kutai Guntung society Bontang, East Borneo. Erau will be held for seven days. In this ceremony, the erau ritual can’t be held if they are not doing the Pelas Benua. Pelas Benua is a ritual that sorrounds the four direction of the wind in Guntung as the form to clean up from the negative things. This ritual using Dewa-Dewa music as accompanist, the belian communicate to Dewa  Semega, He is The God who control the universe. This research using qualitative method with ethnomusicology perspective. Music Dewa-Dewa is ritual music which is specially used in Pelas Benua procession. Music Dewa-Dewa is an ansamble which consist Klentangan, Gong, Gendang and Gimar instrument.                                                                                                  There are three function of Dewa-Dewa music in this ceremony, as communication, ritual function, and physical response. The form of presentation music Dewa-Dewa always can not be separated with form the context of Pelas Benua ceremony and presenting as the ansamble.